PENERAPAN MODEL PEMBELAJARAN HEURISTIK VEE BERBANTUAN MEDIA PUZZLE UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF PESERTA DIDIK PADA MATERI PEMANASAN GLOBAL KELAS X SMAN 2 PEKANBARU - Br Sihombing, Tiurma Febryanti; Rahmad, M.; Azizahwati, Azizahwati (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2024)
this study aims to determine the differences in students cognitive learning outcomes between using heuristic models and puzzle assisted media and conventinonal models in class X global warning material at SMAN 2 Pekanbaru. The research method used is a quantitative method, the population in this study is all class X students of SMAN 2 Pekanbaru and for sample selection using simple random sampling. The sample in this study was two classes, where one class consisted of 43 student. Class X.4 is the control class and X.6 is the experimental class. The instrument in this research was a written test in the form of a post-test consisting of 20 questions. The result of the data obtained are that the average value of cognitive learning outcomes for the experimental class is 87 and the control class is 75, so it can be concluded that the application of the heuristic vee learning model assisted by puzzle media is able to improve the learning outcomes of class X students on global warning material.